Perilaku petani dan kinerja penyuluh pertanian dalam usahatani padi sawah di Kecamatan Baruga Kota Kendari - Minggu Lestari Ningsih; Usman Rianse; Dasmin Sidu (Jurnal Sosio Agribisnis, 2023)
This study aims to determine farmer behavior, the performance of agricultural extension workers, the relationship between farmer behavior and farming productivity, and the influence of agricultural instructor performance on rice productivity in Baruga District, Kendari City. The population in this research is all farmers who cultivate lowland rice and all agricultural instructors whose work area is in Baruga District. Determining the sample of farmers used the Simple Random Sampling method while determining the sample of extension workers used the census method. Determining the number of farmer samples using the Slovin formula. The number of samples determined was 52 farmers and 3 agricultural extension workers. The types and sources of data used are primary data and secondary data. The data analysis used is descriptive analysis, Spearman Rank correlation analysis and simple linear regression analysis. The results of the study show that: farmer behavior in lowland rice farming; The farmer's knowledge level is at the creation level (C6) at 3.85 percent, the farmer's attitude level is at the characterization level (A5) at 74.26 percent, and the farmer's skill level is at the creativity level (P7) at 7.42 percent. The performance of field agricultural instructors in lowland rice farming is in the sufficient category. There is a significant relationship between farmer behavior and lowland rice productivity. With a correlation coefficient of 0.588, it indicates a moderate relationship with a positive relationship direction. The performance of agricultural extension workers has a positive effect on lowland rice productivity. Keywords: farmer behavior; farming; performance of agricultural extension workers; productivity; lowland rice